PRENATAL YOGA TERHADAP TINGKAT KECEMASAN PRIMIGRAVIDA TRIMESTER III - Riza Amalia; Rusmini Rusmini; Diki Retno Yuliani (Jurnal Sains Kebidanan, 2020)
Anxiety in pregnant women often occurs in the third trimester. Anxiety results in prolonged labor, premature birth, LBW (Low Birth Weight). To prevent and reduce anxiety, prenatal yoga as an alternative therapy is given to primigravida pregnant women in the third trimester.The puropose of this study is to find out the influence of prenatal yoga toward anxiety level primigravida in the third trimester in Puskesmas I Kembaran, Banyumas District. This study used quasy experimental with pretest posttest design. The sample in this study are all of primigravida in third trimester, there are 24 pregnant woman in Puskesmas 1 Kembaran. The results showed there were differences in primigravida in third trimester anxiety levels before and after prenatal yoga with p value = 0,000 (p 0.05). There is an influence of prenatal yoga on the level of anxiety primigravida in third trimester. There is a change in the mean level of anxiety of 11,3.